The effects of employee empowerment, teamwork, and employee training on organizational commitment: a case of RISDA, Malaysia - Mohd Yusoff, Nursyazwani (2017)
Organizational commitment becomes an issue in today’s competitive world to become sustain in global. Organizational commitment is defined as the bond employees experience with their organization, employees who are committed to their organization generally feel a connection with their organization, feel that they fit and feel they understand the goals of the organization. Three independent variables has become important factors lead towards organization commitment. Hence, the purpose of this study to identify what are the effects of employee empowerment, teamwork and employee training towards organizational commitment in government sector organization in Malaysia. This research is quantitative research which used self-administered questionnaire to collect data. The data had been successfully collected from 125 respondents and has received 50% of response rate in RISDA by using simple random sampling technique. Then, all the data was analysed and interpreted by using Statistical Package for the Social Sciences (SPSS) software version 20. Based on the result of Pearson Correlation Analysis, the strength of association of the employee empowerment and teamwork are moderate while employee training is weak. Meanwhile, Regression Analysis shows that there are significant relationship between employee empowerment, teamwork and employee training toward organizational commitment. The analysis also revealed that employee empowerment becomes the most influential variable towards organizational commitment.